2002
DOI: 10.1006/jmla.2001.2810
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Semantic Ambiguity: Semantic Competition in Lexical Access

Abstract: There have been several reports in the literature of faster visual lexical decisions to words that are semantically ambiguous. All current models of this ambiguity advantage assume that it is the presence of multiple unrelated meanings that produce this benefit. A set of three lexical decision experiments reported here challenge this assumption. We contrast the ambiguity seen in words like bark, which have multiple unrelated meanings, with words that have multiple related word senses (e.g., twist). In all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
645
13
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(738 citation statements)
references
References 33 publications
70
645
13
10
Order By: Relevance
“…This result suggests that a character with multiple meanings is processed more efficiently, which is congruent with previous naming (Woollams, 2005) and lexical decision (Rodd, Gaskell, & Marslen-Wilson, 2002) studies.…”
Section: Discussionsupporting
confidence: 90%
“…This result suggests that a character with multiple meanings is processed more efficiently, which is congruent with previous naming (Woollams, 2005) and lexical decision (Rodd, Gaskell, & Marslen-Wilson, 2002) studies.…”
Section: Discussionsupporting
confidence: 90%
“…The ambiguity advantage in this LDT is consistent with that reported in Experiment 1 and in many previous studies. The null effect of relatedness is consistent with results reported by Hino et al (2004) and with the claims of Murphy (2001, 2002) but is not consistent with previous reports of a relatedness advantage in LDTs by Azuma and Van Orden (1997) and Rodd et al (2002). We addressed possible reasons for the discrepancy with Azuma and Van Orden's results and also with Rodd et al's results in the Hino et al (2004) article.…”
Section: Resultssupporting
confidence: 72%
“…Not surprisingly, this analysis revealed that switch trials were reliably slower than nonswitch trials, F 1 (1, 30) ϭ 134.18, p Ͻ .01; F 2 (1, 18) ϭ 257.27, p Ͻ .01; and color-naming trials were significantly slower than 5 In a recent article, Finkbeiner, Forster, Nicol, and Nakamura (2004) have suggested that L1 words have more senses than L2 words. See also Finkbeiner (2003) and Rodd, Gaskell, and Marslen-Wilson (2002), who have found that many-sense words are responded to faster than few-sense words. Sense counts were taken from Wordnet (Fellbaum, 1998) Figure 6.…”
Section: Resultsmentioning
confidence: 99%